Disposition to Organizational Learning: A Survey of Selected Construction Industry Organisations in Lagos State, Nigeria - Dada, Martin Oloruntobi; Akpadiaha, Ben; Ologunagba, Modupe Mulikat (Richtmann Publishing, 2012)
The construction industry and her projects are replete with potentials for learning at both the organisational andproject levels. Yet the industry often wastes this opportunity. This research was embarked upon to investigate the disposition ofconstruction industry participants to the use of organisational learning (OL) in the Nigerian construction industry. Data wascollected using a structured questionnaire administered purposively on sixty construction industry organisations operating inLagos, Nigeria. The collected data was subjected to both descriptive and inferential statistical analysis. The findings indicate thatmajority of respondents agreed that ‘Managers ask probing questions and invite input from others in discussions’ and also‘Managers listen attentively’. The study results further indicate that there is no significant difference in disposition toorganizational learning between contracting, consulting, and client organizations within the Nigerian Construction Industry. Thisstudy recommends that a more detailed investigation be made of those items of measure where respondents indicatedisagreements to understand better the underlying phenomena. Measures indicating strong indices of agreement can be furtherexplored for improvement.